MODERN METHODS FOR ESTIMATION OF LIVER FIBROSIS - E. V. Guschina; T. V. Cherednichenko (Детские инфекции (Москва))
In the article we describe different modern methods of estimation of liver fibrosis at chronic viral hepatitis and their role in clinical practice.